Spectrally efficient and low cost time and wavelength division multiplexed passive optical network systems - Salem Mohammed Salem Bindhaiq, 1986-, author; Abu Sahmah Mohd, Supa'at, supervisor; Nadiatulhuda Zulkifli, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2018